Bibliotecas Digitais de Teses e Dissertações: uma estratégia de preservação da memória - Cunha, Jacqueline de Araújo (2009)
The study examined the Brazilian Digital Library of Thesis and Dissertations like a memory preservation strategy. This way, discussed about information, memory, preservation, inclusively digital, as well as the open archives and the open access to scientific information, because they constitute fundamental issues to the comprehension of this topic. The methodology used consisted of bibliographic search on web pages, books, scientific articles and technical reports, as well as with professionals of the institutions that made part of the sample used. It was identified and analyzed information politics adopted by the institutions that made part of the inter-institutional consortium of IBICT, as well as issues related to the kind of software and work methodology that are used. The study concluded that the BDTD is a feasible preservation model and an efficient way to promote the access to thesis and dissertations that historically were limited by geographic and financial barriers. However, to get succeed, its necessary qualified professionals, technical tools and public and institutional information politics as instruments to support the process.